The Function Of Administrative Administration In Improving The Quality Of Education In State Elementary Schools 36 Bengkulu City - Wulandari, Sari; Sari, Jepi Elia (Al-Khair Journal: Management Education, 2025)
Abstrac: The quality of teacher performance is still considered low because the principal’s supervision program has not been optimally implemented. This study aims to evaluate the madrasa principal’s supervision program in improving teacher performance quality at MTsN 2 South Bengkulu. It uses a descriptive qualitative method with the CIPP (Context, Input, Process, Product) evaluation model approach. Data were collected through observation, interviews, and documentation. The research results show that in the context of the madrasah principal’s supervision program, at the input level there are differences in teachers’ pedagogical competencies. At the process level, there are irregularities in the implementation of curriculum-based learning, as well as a lack of innovation in teaching methods. As for the output of the supervision program, teachers are able to carry out the learning process, develop RPS and RPP programs, and create innovations to improve education quality, supported by adequate tools to enhance teacher performance quality. Thus, the evaluation of the madrasah principal’s supervision program can improve the quality of teacher performance. Therefore, it is recommended that to improve teacher performance quality, the madrasah principal’s supervision at MTsN 2 South Bengkulu should be strengthened, even though several technical and cultural challenges still exist. This evaluation provides strategic recommendations for more sustainable and systematic supervision optimization in the future.Keywords: Evaluation, Principal’s Supervision Program, Teacher Performance Quality, MTsN 2 Bengkulu Selatan. Abstrak: Kualitas kinerja guru masih dianggap rendah karena program supervisi kepala madrasah belum diimplementasikan secara optimal. Penelitian ini bertujuan untuk mengevaluasi program supervisi kepala madrasah dalam meningkatkan kualitas kinerja guru di MTsN 2 Bengkulu Selatan. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan model evaluasi CIPP (Konteks, Masukan, Proses, Produk). Data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa dalam konteks program supervisi kepala madrasah, pada tingkat masukan terdapat perbedaan kompetensi pedagogis guru. Pada tingkat proses, terdapat ketidakberaturan dalam implementasi pembelajaran berbasis kurikulum, serta kurangnya inovasi dalam metode pengajaran. Adapun keluaran program supervisi, guru mampu melaksanakan proses pembelajaran, mengembangkan program RPS dan RPP, serta menciptakan inovasi untuk meningkatkan kualitas pendidikan, didukung oleh alat yang memadai untuk meningkatkan kualitas kinerja guru. Dengan demikian, evaluasi program supervisi kepala madrasah dapat meningkatkan kualitas kinerja guru. Oleh karena itu, direkomendasikan agar untuk meningkatkan kualitas kinerja guru, supervisi kepala madrasah di MTsN 2 Bengkulu Selatan diperkuat, meskipun masih terdapat beberapa tantangan teknis dan budaya. Evaluasi ini memberikan rekomendasi strategis untuk optimalisasi supervisi yang lebih berkelanjutan dan sistematis di masa mendatang.Kata kunci: Evaluasi, Program Supervisi Kepala Madrasah, Kualitas Kinerja Guru, MTsN 2 Bengkulu Selatan.